Exceptional preservation of Spaeraphus larvalis in the Miocene Vinchina Formation of western Argentina - Alonso Muruaga, Pablo Joaquin (2016)
The Miocene Vinchina Formation of western Argentina is made up of more than 5100 meters of siliciclastic sediments deposited mostly in fluvial environments, including transitions from braided and meandering, to anastomosed systems. The Upper Member of the unit is characterized by the conspicuous occurrence of braided fluvial deposits, composed of heterolitic multistory channels, gravelly bars, sandy bars, and very thin intercalations of floodplain fines facies, hosting invertebrate and vertebrate trace-fossils assemblages. The present contribution deals with the outstanding preservation of Spaeraphus within these facies. In particular, the ichnofossils studied were recorded at the sole of a massive fine to very fine-grained sandstone bed interbedded with laminated claystones and siltstones, representing overbank sedimentation during flooding episodes. The trace Spaeraphus larvalis occurs as a positive or negative hyporelief. As positive epirelief is characterized by several horizontal burrows displaying raised, often imbricated, oval blocks generating nodular margins, and sometimes developing a discontinuous open medial depression. Occasionally, the medial depression is irregularly filled by smaller blocks. Individual blocks are smooth, subrounded to oval, 1? 4 mm in diameter, and identical in composition to the surrounding matrix. The burrow widths vary from 4 about 12 mm, and their courses are mostly straight with gentle curves with length of decimeter scale. Primary successive branching and intersecting of burrows are also seen. Ongoing research suggests that these traces reflect a shallow dwelling behavior in soft, fine grained substrates subaerially exposed but proximal to the water table as channel margins, interchannel areas, and marginal zones of local ponds.